ナンキョク ヒガシ オングル トウ ニオケル センルイ グンラク ノ ビキショウ ニツイテ - 松田, 達郎; マツダ, タツロウ; MATSUDA, Tatsuro (国立極地研究所, 1964)
P(論文) The microclimatic condition was observed by the specially prepared selfrecording ther-mistor instrument in the community of mosses growing on the south-westward slope at the sandy area (about 500 m from Syowa Base) during the period from February 1961 to January 1962. In summer the community of mosses appears on the surface of the earth (mainly from January to February) but disappears under the snow drift during autumn, winter and spring. The temperature in the mosses community rises as high as +19℃ in summer. Though the air temperature (at Syowa Base) sometimes falls to -40℃, the temperature of mosses under the snow drift does not fall below -20℃ (Fig. 6). Accordingly the mean temperature in the mosses community is higher than the air temperature (Fig. 5). The diurnal change of mosses temperature was recognized in summer remarkably (Fig. 8) but not in winter (Figs. 10 and 11). However, even in summer the cooling rate calculated from the diurnal temperature change is only 1℃ or 2℃ per hour and therefore, the survival rate of microorganisms in mosses seems to be scarcely influenced by the cooling rate. departmental bulletin paper